1986
DOI: 10.1007/bf00020331
|View full text |Cite
|
Sign up to set email alerts
|

Developmental biochemistry of cottonseed embryogenesis and germination XVIII cDNA and amino acid sequences of members of the storage protein families

Abstract: We have sequenced cDNA clones representing each of the three distinct groups of storage proteins of the cotton seed. Characteristics of their mRNAs and derived proteins are given. Dot matrix analysis of the nucleotide and amino acid sequences shows that 2 of these groups of proteins have a great deal of vestigial homology at low stringency and should be considered subfamilies of a single storage protein gene family. The remaining group is quite distinct and should be considered a separate multigene family. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 20 publications
2
49
0
Order By: Relevance
“…In agreement with prior research, which characterized the two principal forms of vicilin as occurring at 48 kDa and 52 kDa (Dure and Chlan 1981;Chlan et al 1986), these vicilin isoforms were also observed as the most abundant proteins on our proteomic maps. Their relative abundances (37% in the AD genome, 36% in the A genome, and 28% in the D genome), however, were a little higher than the previous estimate of 27% by cylindrical SDS-PAGE (Dure and Chlan 1981).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with prior research, which characterized the two principal forms of vicilin as occurring at 48 kDa and 52 kDa (Dure and Chlan 1981;Chlan et al 1986), these vicilin isoforms were also observed as the most abundant proteins on our proteomic maps. Their relative abundances (37% in the AD genome, 36% in the A genome, and 28% in the D genome), however, were a little higher than the previous estimate of 27% by cylindrical SDS-PAGE (Dure and Chlan 1981).…”
Section: Discussionsupporting
confidence: 92%
“…Because mature albumins are typically cleaved into smaller polypeptides that fall outside of the effective separation range of SDS-PAGE, we cannot rule out the possibility that the poor representation of albumin in the present protein profiles may be due to a technical limitation of 2-DE profiling; however, other estimates of protein abundances, which rely on amino acid composition, concur with our assessment. That is, cotton seeds have been characterized as deficient in sulfur-containing amino acids, indicating that sulfur-rich proteins (such as albumin) constitute a low fraction of the total seed proteins (Bressani et al 1966;Chlan et al 1986;Galau et al 1991Galau et al , 1992.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence d a t a from a non-legA c D N A clone o f Pisum (with a b o u t 42% a m i n o acid sequence identity to legA) and o f two legumin genes from Viciafaba, also indicates a similar glutamic acid and aspartic acid-rich region[12,40]. In addition, the h o m o l o g o u s cotton genes described by Chlan et al[7] also contain such a region. Large insertions and deletions o f the types seen in the ot peptide are not seen in the/3 peptidecoding p o r t i o n s o f the genes compared.…”
mentioning
confidence: 98%
“…6. The deduced amino acid sequence of pumpkin preproglobulin was compared with those of precursor proteins of soybean glycinin [25], pea legumin [27], cotton /3 globulin [31] and rape 11-S globulin [32] (Fig. 7).…”
Section: Resultsmentioning
confidence: 99%